Storytelling in the Classroom: Why it Matters in Event Marketing Education - Vergara, Raymond Allan G.; Vergara, Kimberly Christie S. (Future Science / FSH-PH Publications, 2023)
This study examines why students value storytelling in the classroom and explores how they learn event marketing through this pedagogical tool. Using a post course assessment survey, this qualitative study finds that students value storytelling because stories make it easier for them to understand and digest the subject matter in fun and relatable way. Listening to stories allow them to take on a different and new perspective, allowing them to make sense of new information and master concepts. Storytelling can be entertaining and immersive, which helps develop in students positive learning-related attitudes, values, and beliefs.